EFFICACY OF NEURAL MOBILIZATION AND ADVICE ON POSTURAL CORRECTION IN CERVICOGENIC HEADACHE: A CASE REPORT (International Journal of Physiotherapy, 2016)
Background: This report was based on a patient who was suffering from cervicogenic headache. Patient required intense treatment for pain relief due to this headache. The main aim of this report is to explain the management of cervicogenic headache by using postural correction and neural mobilization techniques.Method: A 42 year old female patient was suffering from headache since 20 years with no definite cause. Her chief complaints were chronic, gradual bilateral fronto-temporal headache associated with pain radiating to right arm, which has led to an inability to do household work. The aggravating factors were stress, watching television, use of mobile phone. The relieving factors were rest, or taking analgesics. The headache usually increased by evening.Results: Various tests which included both musculoskeletal and neurological were used to assess the patient. The outcome measures were the headache impact test, VAS (visual analogue scale) and headache diary. After one month intervention for five days a week, patient reported decreased frequency and intensity of headache and this improvement was associated with the analysis of chief complaints along with observation and examination by physical therapist. Further use of manual therapy, i.e., daily neural mobilization, stretching and strengthening of appropriate muscles proved to be highly beneficial.Conclusion: This study concluded that neural mobilisation is also an effective treatment in treating cervicogenic headache.